IDEOLOGICAL FOUNDATIONS OF IBN SINA'S DOCTRINE OF "BODY" AND "SOUL" IN ANCIENT PHILOSOPHY - Dildora Akhatova (Western European Studies, 2024)
The article talks about the fact that the soul is a philosophical concept representing the spiritual-spiritual, immaterial beginning, and in the history of philosophical thinking, the soul is interpreted from different methodological positions. In particular, if panlogism interprets the soul as a logical concept, the supporters of pantheism study the soul as the substance of the world.
Keywords: soul; philosopher; body; doctrine